Vznik ameriškega dokumentarnega romana in njegove postmoderne razsežnosti - Flis, Leonora (Primerjalna književnost, 2007)
The rise of the nonfiction novel in the U.S. in the 1960s coincides with the birth of New Journalism. Both narratives share a principle of combining references to empirical reality with techniques of fiction. This reflects postmodern poetics, which favors hybrid genres and renounces the "grand narrative".
Keywords: American literature; ameriška književnost; postmodernizem; dokumentarni roman; fikcionalnost